Late Holocene vegetation dynamics and lake geochemistry at Laguna Miranda, XI Region, Chile Dinámica vegetaciónal y geoquímica lacustre del Holoceno tardío en Laguna Miranda, XI Región, Chile - S. G. HABERLE; J. M. SZEICZ; K. D. BENNETT (Revista Chilena de Historia Natural, 2000)
Palynological and geochemical analysis of late Holocene lake sediments and dendrochronological analysis of Pilgerodendron in a volcanically active region of southern Chile reveal the long-term impact of a series of tephra fall events and tectonic activity on lake sedimentation and local vegetation. An upper 0,75 m core overlaps with a 4,35 m long Livingstone piston core to give a 4,60 m long sediment record, extending back to 4800 yr BP. Geochemical data shows the shift from allogenic dominance to authigenic and biogenic dominance as waterlogged soils developed within the catchment. This is presumed to have occurred under the influence of continued addition of nutrients to the catchment from tephra deposition and the associated high sedimentation rates. The palynological record from this site is dominated by Nothofagus dombeyi-type and Filicales. The most prominent changes in the pollen record, however, are the gradual decline in Podocarpus nubigena pollen throughout the last 4800 yr; the appearance and increase of Gramineae pollen during the past 2100 yr; and the rapid increase in the pollen of Pilgerodendron uviferum within the past 300-400 yr. Pilgerodendron tree-ring analysis and the pollen results over the last 400 years show that the most recent expansion of Pilgerodendron at the northern and eastern margins of this site is a response to either, periodic tectonic induced watertable changes, or is part of a long-term trend in gymnosperm growth around a shallowing lake margin. The decline of shade-intolerant trees such as Weinmannia and Podocarpus within a Nothofagus-rich forest community towards an increased presence of Pilgerodendron and Gramineae (likely Chusquea bamboo), that began over 2100 yr BP, may have been due as much to autogenic processes such as a change in the disturbance regime resulting in the development of waterlogged soils, rather than to an episode of climate change. It is important to recognise the potential effects of autogenic processes that may result from disturbance such as volcanic/tectonic activity in reconstructing past vegetation dynamics from pollen records Análisis palinológicos y geoquímicos de sedimentos lacustres del holoceno tardío y análisis dendrocronológicos de Pilgerodendron uviferum en una zona volcánica activa del sur de Chile revelan el impacto a largo plazo de diversas caidas de tefra y actividad tectónica en la sedimentación lacustre y la vegetación de la zona. Una sección sedimentaria superior de 0,75 m traslapa una columna de pistón Livingstone de 4,35 m de largo para dar un registro de sedimentación de 4,60 m de longitud extendiéndose 4800 años AP. Datos geoquímicos muestran el cambio de dominancia alogénica a dominancia autígena y biogénica según se formaban los terrenos anegadizos dentro de la cuenca. Se presume que esto pudo producirse bajo la influencia de la llegada constante de nutrientes a la cuenca del lago procedentes del depósito de materias volcánicas conjuntamente con una alta sedimentación. El registro palinológico de este lugar está dominado por el tipo Nothofagus dombeyi y Filicales. Los cambios más notables que registra el polen son, no obstante, la declinación gradual del polen Podocarpus nubigena durante los últimos 4800 años; la aparición y aumento del polen Geamineae durante los pasados 2100 años; y el rápido aumento del polen Pilgerodendron uviferum en los últimos 300 a 400 años. El análisis de los anillos de leño de Pilgerodendron y los resultados que da el polen en los últimos 400 años muestran que la expansión más reciente de Pilgerodendron en las márgenes norte y este del lugar es una respuesta, bien a cambios periódicos de la capa freática por interacción tectónica, o es parte de un lento proceso de desarrollo de gimnospermas en las márgenes poco profundas del lago. La disminución de Weinmannia y Podocarpus, hace alrededor de 2100 años AP, se podría deber a procesos autogénicos resultando en el desarrollo de terrenos anegadizos, o a cambios en el régimen de perturbación, más bien que a un episodio de enfriamiento climático. En la reconstrucción de la dinámica de vegetaciones pasadas y partiendo de los registros del polen, es importante reconocer los efectos potenciales de los procesos autogénicos que pueden derivarse de perturbaciones tales como actividad volcánico/tectónica